Correlate Attitudes Toward LGBT and Sexism in Spanish Psychology Students - López-Sáez, Miguel Ángel; García-Dauder, Dau; Montero, Ignacio (Frontiers in Psychology, 2020)
The present study evaluates the correlations between sexism, homonegativity, binegativity, pro-trans attitudes, political affiliation, contact with LGBT individuals and perceived stigma among psychology students. A study was conducted with 655 cis women (471 heterosexuals, 179 bisexuals and lesbians) and 174 cis men (120 heterosexuals, 54 bisexuals and gays). Descriptive, multivariate analysis of variance, bivariate correlations and multiple regression were used. In general, the groups of men and heterosexuals obtained higher negativity scores and lower acceptance scores, with significant correlations being more frequent in the heterosexual group. Predictive models confirmed the literature on social and ideological conservatism.